Age and gender differences in misperceptions of body shape in a Taiwanese population - Weng, Hui-Ching; Chang, Sheng-Mao; Hsu, Jason C.; Yang, Yung-Ning; Lin, Chung-Ying (Journal of eating disorders, 2023)
Most studies of body size perception have been performed in adolescents, and most focus on gender differences in accurate perception of body size. This study investigated misperceptions of body sizes among males and females at different stages of adulthood in Taiwan. In-person home interviews were used to proportionally and randomly select 2095 adult men and women to answer the East Asian Social Survey. Participants were divided into 18-39, 40-64, and 65 + age groups. The main variables analyzed were self-perceived body size and standardized BMI. Women, unlike men, were more likely to misperceive their body size as being overweight (OR = 2.92; p < .001). People with higher self-perceived social status were less likely to misperceive themselves as overweight (OR = 0.91; p = .01). People with college educations were 2.35 times more likely to overestimate their body size as being heavier than they were (p < .001) and less likely to underestimate it as being thinner than they were (OR = 0.45; p < .001). Women 18-35 and 36-64 years old were 6.96 and 4.31 times more likely (p < .001) to misperceive themselves as being overweight than women 65 or older, who were more likely to misperceive themselves as being too thin. There were no significant differences in body size misperceptions among the three age groups of adult men (p > .05). We found no different significant discrepancies between self-perceived body size and actual BMI between the older men and women (p = .16). However, younger and middle-aged men were 6.67 and 3.1 times more likely to misperceive themselves as being too thin than women in their same age groups (OR = 0.15 and OR = 0.32, respectively). Age and gender affect self-perceptions of body size in Taiwan. Overall, women are more likely than men to misperceive themselves as being too big, and men are more likely than women to misperceive themselves as too thin. Older women, however, were more likely to misperceive themselves as being too thin. Clinicians and health educators should know that people's perceptions and concerns regarding their body size vary by age and gender.